-(4y+2)-(-3y-5)=-2

Simple and best practice solution for -(4y+2)-(-3y-5)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(4y+2)-(-3y-5)=-2 equation:


Simplifying
-1(4y + 2) + -1(-3y + -5) = -2

Reorder the terms:
-1(2 + 4y) + -1(-3y + -5) = -2
(2 * -1 + 4y * -1) + -1(-3y + -5) = -2
(-2 + -4y) + -1(-3y + -5) = -2

Reorder the terms:
-2 + -4y + -1(-5 + -3y) = -2
-2 + -4y + (-5 * -1 + -3y * -1) = -2
-2 + -4y + (5 + 3y) = -2

Reorder the terms:
-2 + 5 + -4y + 3y = -2

Combine like terms: -2 + 5 = 3
3 + -4y + 3y = -2

Combine like terms: -4y + 3y = -1y
3 + -1y = -2

Solving
3 + -1y = -2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -1y = -2 + -3

Combine like terms: 3 + -3 = 0
0 + -1y = -2 + -3
-1y = -2 + -3

Combine like terms: -2 + -3 = -5
-1y = -5

Divide each side by '-1'.
y = 5

Simplifying
y = 5

See similar equations:

| 7x+9y=11 | | ar+ar^2=9 | | 3+6p-2=5p+29-3p | | 2y+7=5y-8 | | ar+ar=9 | | 3(x-1)=4(3+3x) | | 3t+4t=42 | | 2a=r | | 8-2(4x-2)=-2 | | 2-2(6x-2)=-4 | | -10.9x=98.1 | | 4x-6+6x=5(4x-2)+2 | | 5m=-35 | | 8x+9=8(x+3) | | -13a-48=-5a | | 2.6q-3.5-5.7q=-4.1q-5.3 | | 2.6q-3.5-5.7=-4.1q-5.3 | | 4x-9y=-16 | | 7x+2=7(x-9) | | 10x+6-3=9x-2 | | 3a+5a=24 | | x^2+y^2+12x-26y+61=0 | | 4x-9y=-6 | | x+60=30 | | -5c+31=1 | | s-21=-11 | | 2(3y+1)=-16 | | -3(X+7)=-30 | | 7x-3(4-2x)=6(x-5)-12 | | 59+6y-10=17y-14-2y | | 14x-(2x+4)=12 | | 5t-4=5t+5 |

Equations solver categories